Arsitektur Kolonial Kota Madiun: Analisis Gaya, Sistem Bangunan, dan Adaptasi Tropis dari Indische Empire hingga Nieuwe Bouwen - Uswatun Hasanah (Journal of Engineering and Applied Technology, 2025)
Colonial architecture in Madiun City reflects a complex interaction between political power, technological development, and environmental adaptation during the Dutch colonial period. As an administrative center of the Madiun Residency, the city experienced architectural transformation from the monumental Indische Empire style to the more rational and functional Nieuwe Bouwen approach. This study examines architectural styles, building systems, and tropical adaptation strategies embedded in colonial buildings in Madiun. The findings indicate that early colonial architecture emphasized symmetry, massive walls, and classical proportions, while later developments adopted reinforced concrete structures and simplified forms. Despite technological modernization, colonial buildings consistently integrated passive design strategies, including wide verandas, high ceilings, large openings, and strategic orientation to optimize ventilation and thermal comfort. The use of local materials combined with European construction techniques demonstrates a pragmatic response to tropical climate conditions. These architectural characteristics position colonial buildings in Madiun as valuable historical artifacts and as relevant references for contemporary tropical architecture. Understanding their design principles contributes to heritage conservation efforts and offers insights into sustainable architectural practices rooted in historical experience.